2018
DOI: 10.1002/jbm.a.36362
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous biological factors modulated by substrate stiffness regulate endothelial differentiation of mesenchymal stem cells

Abstract: During the process of tissue regeneration facilitated by stem cells, physical properties of a scaffold affect behavior and activities of the cell. To enhance differentiation of human mesenchymal stem cells (MSCs) into endothelial-like cells (ELCs), we used electrospun fibrous substrates with different stiffness to enhance the differentiation. A simple method of annealing with different lengths of treatment time was employed to modulate stiffness of electrospun fibrous substrates without changing their chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…VEGF has been widely reported to guide MSC differentiation to ECs, which are a reliable cell source for successful vascular tissue engineering endeavors. 23,36,37 For instance, Du et al found that, during endothelial differentiation, MSCs induced by VEGF showed EC phenotypes in culture. 38 Therefore, in our study, the effects of PCL/GPs and PCL/VGPs on MSCs were investigated via qPCR and WB to verify their biofunctionability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGF has been widely reported to guide MSC differentiation to ECs, which are a reliable cell source for successful vascular tissue engineering endeavors. 23,36,37 For instance, Du et al found that, during endothelial differentiation, MSCs induced by VEGF showed EC phenotypes in culture. 38 Therefore, in our study, the effects of PCL/GPs and PCL/VGPs on MSCs were investigated via qPCR and WB to verify their biofunctionability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition to culturing MSCs on GP-and VGP-loaded PCL fibrous scaffolds, MSCs cultured on PCL scaffolds were treated as negative controls, while MSCs cultured on PCL scaffolds with 50 ng/mL VEGF during differentiation were set as positive controls (denoted as PCL/VEGF). 23 Culture medium was changed every 2 days. After culturing on different scaffolds for 10 days, the total RNA in MSCs was extracted using Trizol (Invitrogen, USA), reverse-transcribed using a high capacity cDNA reverse transcription kit (AB Applied Biosystems, USA) following the manufacturer's instructions, and then amplified using SYBR Green Supermix (Bio-Rad, USA) with primers for detecting NANOG, octamer-binding transcription factor 3/4 (OCT 3/4), platelet endothelial cell adhesion molecule (CD31), von Willebrand factor (vWF), SOX 18, vascular endothelial growth factor receptor 1 (VEGFR1), vascular endothelial growth factor receptor 2 (VEGFR2), and the internal control ubiquitin C (UBC), as listed in Table 1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering scaffolds hold great potential in the fields of regenerative medicine and clinical trials by regulating cell behaviors and tissue reconstruction. 1,2 By far, numerous investigations have reported various methods, including electrospinning, 3 decellularized extracellular matrix, 4 and 3D printing, 5 to produce tissue engineering scaffold with predeterminedtopographic and physical properties inspired by the extracellular matrix. For instance, in our previous study, a polycaprolactone (PCL) self-induced nanohybrid shish-kebab structure consisting of PCL nanofibers and spaced PCL crystal lamellae grown on the fibers was employed to regulate cell affinity and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue engineering scaffold holds great potential in the fields of regenerative medicine and clinical trials by regulating cell behaviors and tissue reconstruction . By far, abundant investigations have reported various kinds of engineered scaffolds inspired by the extracellular matrix (ECM), including electrospun scaffold, decellularized extracellular matrix, and hydrogel . Among these, electrospun scaffolds may be inferior to serve in a compressive environment, while the decellularized extracellular matrix may bring immunoreaction and contagion if the original cellular components are not fully removed .…”
Section: Introductionmentioning
confidence: 99%